Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the average rate of change of the function [tex]\( f(x) = 2x^2 - 3 \)[/tex] between the points [tex]\((2, 1)\)[/tex] and [tex]\((2+h, f(2+h))\)[/tex], follow these steps:
1. Identify the coordinates:
- The first point is [tex]\((2, 1)\)[/tex].
- The second point is [tex]\((2+h, f(2+h))\)[/tex].
2. Compute [tex]\(f(2+h)\)[/tex]:
- Here, [tex]\(f(x) = 2x^2 - 3\)[/tex].
- Therefore, [tex]\(f(2+h) = 2(2+h)^2 - 3\)[/tex].
3. Expand and simplify [tex]\(f(2+h)\)[/tex]:
[tex]\[ f(2+h) = 2(2+h)^2 - 3 \][/tex]
[tex]\[ (2+h)^2 = 4 + 4h + h^2 \][/tex]
[tex]\[ f(2+h) = 2(4 + 4h + h^2) - 3 = 8 + 8h + 2h^2 - 3 = 5 + 8h + 2h^2 \][/tex]
4. Calculate the average rate of change:
- The formula for the average rate of change between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] of the function [tex]\(f\)[/tex] is:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
- In our case, this becomes:
[tex]\[ \frac{f(2+h) - f(2)}{(2+h) - 2} \][/tex]
5. Substitute the values:
- We know [tex]\(f(2) = 2(2)^2 - 3 = 8 - 3 = 5\)[/tex].
- So:
[tex]\[ \frac{f(2+h) - f(2)}{(2+h) - 2} = \frac{(5 + 8h + 2h^2) - 5}{h} = \frac{8h + 2h^2}{h} \][/tex]
6. Simplify the expression:
[tex]\[ \frac{8h + 2h^2}{h} = \frac{h(8 + 2h)}{h} = 8 + 2h \][/tex]
Therefore, the expression in terms of [tex]\(h\)[/tex] that gives the average rate of change between [tex]\((2, 1)\)[/tex] and [tex]\((2+h, f(2+h))\)[/tex] is:
[tex]\[ 8 + 2h \][/tex]
1. Identify the coordinates:
- The first point is [tex]\((2, 1)\)[/tex].
- The second point is [tex]\((2+h, f(2+h))\)[/tex].
2. Compute [tex]\(f(2+h)\)[/tex]:
- Here, [tex]\(f(x) = 2x^2 - 3\)[/tex].
- Therefore, [tex]\(f(2+h) = 2(2+h)^2 - 3\)[/tex].
3. Expand and simplify [tex]\(f(2+h)\)[/tex]:
[tex]\[ f(2+h) = 2(2+h)^2 - 3 \][/tex]
[tex]\[ (2+h)^2 = 4 + 4h + h^2 \][/tex]
[tex]\[ f(2+h) = 2(4 + 4h + h^2) - 3 = 8 + 8h + 2h^2 - 3 = 5 + 8h + 2h^2 \][/tex]
4. Calculate the average rate of change:
- The formula for the average rate of change between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] of the function [tex]\(f\)[/tex] is:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
- In our case, this becomes:
[tex]\[ \frac{f(2+h) - f(2)}{(2+h) - 2} \][/tex]
5. Substitute the values:
- We know [tex]\(f(2) = 2(2)^2 - 3 = 8 - 3 = 5\)[/tex].
- So:
[tex]\[ \frac{f(2+h) - f(2)}{(2+h) - 2} = \frac{(5 + 8h + 2h^2) - 5}{h} = \frac{8h + 2h^2}{h} \][/tex]
6. Simplify the expression:
[tex]\[ \frac{8h + 2h^2}{h} = \frac{h(8 + 2h)}{h} = 8 + 2h \][/tex]
Therefore, the expression in terms of [tex]\(h\)[/tex] that gives the average rate of change between [tex]\((2, 1)\)[/tex] and [tex]\((2+h, f(2+h))\)[/tex] is:
[tex]\[ 8 + 2h \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.